2023
DOI: 10.3390/biomedicines11082239
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelium in Cardiovascular Sequelae of Long COVID

Abstract: The global action against coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2 infection, shed light on endothelial dysfunction. Although SARS-CoV-2 primarily affects the pulmonary system, multiple studies have documented pan-vascular involvement in COVID-19. The virus is able to penetrate the endothelial barrier, damaging it directly or indirectly and causing endotheliitis and multi-organ injury. Several mechanisms cooperate to development of endothelial dysfunction, including endothelial cell injury and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 172 publications
0
13
0
1
Order By: Relevance
“…It has been found that endothelial dysfunction plays a pivotal role in the development of many of the immediate complications associated with COVID-19, including acute cardiovascular events and thrombosis. Additionally, it is also linked to the onset of various post-COVID-19 signs and symptoms [ 6 , 24 ]. Finally, patients with pre-existing comorbidities may have lower functional organ reserve and, therefore, be more likely to develop post-COVID-19 syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that endothelial dysfunction plays a pivotal role in the development of many of the immediate complications associated with COVID-19, including acute cardiovascular events and thrombosis. Additionally, it is also linked to the onset of various post-COVID-19 signs and symptoms [ 6 , 24 ]. Finally, patients with pre-existing comorbidities may have lower functional organ reserve and, therefore, be more likely to develop post-COVID-19 syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, patients with cardiac and cardiovascular diseases are more likely to develop post-COVID-19 syndrome [ 5 ]. Several authors underlined that both comorbidities and COVID-19 itself worsen endothelial dysfunction, which is currently deemed to be one of the most important determinants in the development of severe COVID-19 and in the persistence of several post-COVID-19 signs and symptoms [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In such a context, a higher prevalence of acute coronary syndromes, acute pulmonary embolism, deep veinous thrombosis and ischemic stroke has been reported as a consequence of the persistence of inflammation, cytokine storm, microvascular damage, and stress-induced cardiomyopathy [ 95 ].…”
Section: Endothelial Dysfunction In Covid-19 With Associated Metaboli...mentioning
confidence: 99%
“…1 , 2 O efeito citopático do vírus no endotélio, juntamente com o dano endotelial como consequência da inflamação sistêmica, tem sido associado a eventos cardiovasculares como miocardite, infarto do miocárdio, arritmias, e eventos tromboembólicos. 3 …”
unclassified
“…1 , 2 The cytopathic effect of the virus on the endothelium, along with endothelial damage as a consequence of systemic inflammation, has been associated with cardiovascular events such as myocarditis, myocardial infarction, arrhythmias, and thromboembolic events. 3 …”
mentioning
confidence: 99%